THE EFFECT OF PRECURSOR CONCENTRATION, pH OF THE SOLUTION AND CARBONATION DURATION ON CACO3 PARTICLE SIZE VIA CARBONATION METHOD - Febrida, Renny; Faza, Yanwar (Universitas Baiturrahmah, 2024)
Background. There are multiple techniques for generating CaCO3, one of which is the carbonation method. Currently, the particle size of CaCO3 is primarily determined by the combined influence of various variables. Objective. This study investigates the effect of precursor concentrations, pH of the solution, and carbonation duration on the size of CaCO3 particles Methods. The type of research in this study is experimental laboratory with a descriptive presentation of data. This study is divided into two stages: first, synthesis of CaCO3 with different concentration of precursors and carbonation duration. Second, it used different pH value of the solution and carbonation duration. The particle size of CaCO3 were characterized using the Particle Size Analyzer (PSA) (Horiba Scientific SZ-100 Nanopartica). Result. The result show the smallest CaCO3 at first stage, 548 nm, obtained at concentration of 0.75 M with carbonation duration of 30 minutes. The largest CaCO3-size, 6194 nm, is seen at a 0.5 M concentration with a carbonation duration of 10 minutes. The second stage show the smallest particle size, 1165 nm, obtained at a pH value of 8 with a carbonation duration of 60 minutes. Meanwhile, the largest size, 5621 nm, is obtaining at a pH value of 9 with a carbonation duration of 90 minutes Conclusion. The concentration of precursors and the duration of carbonation have no effect on the size of CaCO3 particles, however the pH value of the solution may affect the particle size of CaCO3. It is directly proportional to the pH value of the solution